A very rare complication of vesico-uterine fistula following lower segment caesarean section. (November 2017) - Mei Goh, Yan; Bijoor, P; Andrews, Henry
Abstract : Introduction: Vesico-uterine fistula (VUF) is a recognised but rare complication following lower segment caesarean section with an incidence of less than 4% of all urogenital fistulae. Patients commonly present with urinary incontinence, cyclical haematuria, amenorrhoea, infertility and spontaneous first trimester abortions. Presentation can be immediate or delayed. Case description: A 34-year-old lady presents with an eight-day history of continuous urinary leakage, following LSCS. She had the operation due to failure to progress during labour. She was discharged home after 2 days only to re-present. Speculum examination revealed drainage of clear fluid from the vagina. A vesico-vaginal fistula (VVF) was suspected and she underwent intravenous urogram (IVU) and CT abdomen and pelvis. Radiological findings revealed a suspected fistula but its precise anatomy was uncertain, hence a diagnosis was not made. She underwent examination under anaesthesia, cystoscopy, colposcopy and hysteroscopy, which revealed a small defect in the dome of the bladder and further advancement of the scope led to an entry into a second confined space – the uterus. Clearly there was communication between these spaces. A hysteroscopy revealed missing anterior aspect of the cervix, and proximal to this was the fistula. A urinary catheter was inserted and elective laparotomy planned in six weeks to allow for uterine involution. On the day of her operation, the patient reported cessation of urinary leakage and felt there was no significant vaginal discharge. The assumption was that her fistula had closed spontaneously. A formal cystogram was performed showing the presence of contrast within two cavities. Methylene blue dye was instilled into the bladder via the urinary catheter. Blue staining on the cervix end of the tampon confirmed a patent fistula tract. She underwent laparotomy where the bladder was bivalved to separate it from the anterior aspect of the uterus and cervix, the fistulous tract was excised, and the bladder repaired. An omental 'tongue' was place as interposition between the uterus and the bladder. Her post-operative recovery was uneventful and she was discharged home. On review 6 weeks post-operatively, she had made a full recovery with no further urinary leakage. Results and Conclusions: VUF is an unusual complication of LCSC, and presentation is very variable, from frank urinary leakage to vaginal discharge. What makes it unique is a competent cervix, which closes and allows urine to be trapped in to the uterus. This creates the variability of the intensity of discharge - if at all and other non-specific presentation as previously alluded to. A high index of suspicion is therefore required to make this diagnosis, as cystograms may not necessarily fill the uterus, especially if already involuted. For the same reasons, VUF may present early following caesarean section or as a delayed presentation several years later. Patients may not necessarily present with urinary leakage. Take home message: A double ring overlap should be looked for, in cystograms, and lateral views must be obtained. A methylene blue test can be helpful if carefully conducted. A pelvic 'scopy' – cystoscopy, hysteroscopy and colposcopy are part of required armamentarium in making a diagnosis. CT and MRI scans could also be employed. Once a diagnosis is made, repairs of VUF is similar to VVF.